2021
DOI: 10.3390/axioms10030203
|View full text |Cite
|
Sign up to set email alerts
|

The Soliton Solutions for Some Nonlinear Fractional Differential Equations with Beta-Derivative

Abstract: Nonlinear fractional differential equations have gained a significant place in mathematical physics. Finding the solutions to these equations has emerged as a field of study that has attracted a lot of attention lately. In this work, He’s semi-inverse variation method and the ansatz method have been applied to find the soliton solutions for fractional Korteweg–de Vries equation, fractional equal width equation, and fractional modified equal width equation defined by Atangana’s conformable derivative (beta-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 53 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Using the traveling wave ansatz, Baiswas [17], studied the generalized Kawahara equation and derived a solitary wave solution for the family of the Kawahara equation. A lot of effective methods are applied to study the exact solutions, which makes the research more abundant [18][19][20][21][22][23]. Wang [24] used ansatz method to derive the exact solitary wave solution for the generalized Korteweg-de Vries-Kawahara (GKdV-K) equation.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Using the traveling wave ansatz, Baiswas [17], studied the generalized Kawahara equation and derived a solitary wave solution for the family of the Kawahara equation. A lot of effective methods are applied to study the exact solutions, which makes the research more abundant [18][19][20][21][22][23]. Wang [24] used ansatz method to derive the exact solitary wave solution for the generalized Korteweg-de Vries-Kawahara (GKdV-K) equation.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…A short list can be made as follows. The sub-equation method (see, [20][21][22][23]), the sinecosine method (see, [24]), Laplace transform method (see, [25]), the auxiliary equation method (see, [26]), direct algebraic method (see, [27]), Kudryashov method (see, [28]), the variational iteration method (see, [29]), the first integral method (see, [30]), F-expansion method (see, [31,32] ), ( ) ¢ G G 2 extension method (see, [33][34][35]), He's semi inverse method (see, [36]), ansatz approach (see, [37]) are some examples.…”
Section: Introductionmentioning
confidence: 99%
“…The whole of these FNEEs, FNPDEs, FNDDEs remains an ongoing task due to the fact that, the power of memory effect is of great interest in the modeling field's. From the mathematical point of view, the classical systems (integer-order derivatives modeling) are not thoughtfully to address this memory effect issue [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Obviously, different researchers demonstrated that, through the fractional-order derivatives (non-integer operators) it is possible to carry out more on memory effect.…”
Section: Introductionmentioning
confidence: 99%